ANALISIS PELAPORAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KOTA MANADO - Salatnaya, Riseda; Morasa, Jenny; Budiarso, Novi Swandari (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2022)
This research is motivated by the occurrence of successive findings regarding the management and reporting of BOS funds, and the problems faced by the Manado City Government, namely the delay in reporting the details of BOS fund assets which is one of the determinants of the balance sheet value in the Regional Government Financial Statements. Therefore, this study was conducted to analyze the reporting of BOS funds at the Education and Culture Office of Manado City, the objectives of which are limited to: knowing the process of reporting assets of School Operational Assistance (BOS) funds from the Manado City Education and Culture Office, the constraints causing delays in reporting BOS funds assets as a determinant of the balance sheet value, and the efforts of the Manado City Government to overcome obstacles in reporting BOS fund assets. This study uses a qualitative research method with a case study approach, and the results are analyzed using the Miles and Huberman Model analysis technique. Informants in this study were recipients and processors of BOS fund reports at the Manado City Regional Finance and Assets Agency, Manado City BOS Management Team and School BOS Management Teams. The results of the study found that the reporting process for BOS funds, both as a whole and specifically for asset reports, was in accordance with applicable regulations. Constraints encountered in reporting are human resources, incompatibility of accounts and non-compliance. Efforts made by the Manado City Government to overcome obstacles are mentoring and assisting operator personnels, reclassifying accounts as a result of reconciliation and imposing sanctions.